2021
DOI: 10.1007/s10588-021-09339-8
|View full text |Cite
|
Sign up to set email alerts
|

ReOpen demands as public health threat: a sociotechnical framework for understanding the stickiness of misinformation

Abstract: In the absence of a national, coordinated, response to COVID-19, state and local representatives had to create and enforce individualized plans to protect their constituents. Alongside the challenge of trying to curb the virus, public health officials also had to contend with the spread of false information. This problematic content often contradicted safeguards, like masks, while promoting unverified and potentially lethal treatments. One of the most active groups denying the threat of COVID is The Reopen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This erosion of trust costs the United States between $50 and $300 million daily (Bruns et al 2021), contributes to an ongoing public health crisis (Jennings et al 2021), and dilutes democratic integrity (Swann 2022). A range of scholars have demonstrated how propagandists make use of information systems to spread problematic content (Benkler, Farris, and Roberts 2018;Chen et al 2021;Nisbet, Mortenson, and Li 2021;Ognyanova et al 2020;Tripodi 2021). In this study, we take up the question of how libraries and librarians could become a central part of the solution.…”
Section: Libraries Combating Disinformation: From the Frontline To Th...mentioning
confidence: 99%
“…This erosion of trust costs the United States between $50 and $300 million daily (Bruns et al 2021), contributes to an ongoing public health crisis (Jennings et al 2021), and dilutes democratic integrity (Swann 2022). A range of scholars have demonstrated how propagandists make use of information systems to spread problematic content (Benkler, Farris, and Roberts 2018;Chen et al 2021;Nisbet, Mortenson, and Li 2021;Ognyanova et al 2020;Tripodi 2021). In this study, we take up the question of how libraries and librarians could become a central part of the solution.…”
Section: Libraries Combating Disinformation: From the Frontline To Th...mentioning
confidence: 99%
“…Tripodi [ 55 ] utilized a sociotechnical framework to analyze the sociopolitical and technological factors contributing to misinformation’s spread and persistence. They argue that the continuation of this misinformation is due to a complex interplay of social and technological factors, including political polarization, the use of social media platforms to spread misinformation, and the amplification of misinformation by influential individuals and organizations.…”
Section: Resultsmentioning
confidence: 99%
“…The study also highlights the potential public health consequences of the persistence of this misinformation, including increased transmission of viruses and decreased compliance with public health guidelines. The authors concluded that addressing this issue will require a multifaceted approach that considers the social and technological factors contributing to the spread of misinformation [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As COVID policies spurred RWE activism in the general public (Tripodi 2021), lockdowns and mask and vaccine mandates prompted fierce opposition from RWE organizations, including the CSPOA (Chammah 2020). Sheriffs vocally resisted mask mandates, articulating RWE‐consistent views like anti‐federalism with Sheriff Bieber (Shawano County, Wisconsin), “Health Code orders should never encroach the Constitutional rights of the American people.…”
Section: Right‐wing Extremism Targets Sheriffsmentioning
confidence: 99%